Temporal Variation of Microzooplankton Community in Prasae Estuary, The Gulf of Thailand - Jitchum, Pailin; Duangdee, Teerapong (Journal of Fisheries and Environment, 2015)
The microzooplankton community was studied in February, June and November 2008 in Prasae Estuary, Rayong Province, located along the eastern coast of the Inner Gulf of Thailand. Microzooplankton was collected by horizontal hauling with a 125 μmmesh size plankton net. Twelve stations were used for sampling in three study areas of Prasae Estuary, namely the inner riverine, estuarine and marine sections. Several hydrographical parameters were measured. Thirty-two groups of microzooplankton were recorded. The holoplankton was more abundant than meroplankton. The most diverse sample was found in the marine section (32 groups), followed by the estuarine mouth (23 groups), and the inner riverine area (16 groups). The pooled data of all samples showed the highest average abundance in the estuarine area, followed by the inner riverine area, and the marine section (2,679 ± 1,563, 1,755 ± 1,043 and 1,097 ± 877 ind. m-3, respectively). The dominant group was copepods, comprising between 70-87% of the total microzooplankton abundance. The microzooplankton community showed temporal variation in abundance in the annual cycle. The inner riverine and marine sections had the highest abundance in February while the estuarine mouth showed the highest abundance in June. In this regard, the monsoon season might be the main factor influencing the microzooplankton community in this study area.